ChemInform Abstract: Efficient Approach to Mesoionic Triazolo[5, 1‐a]isoquinolium Through Rhodium‐Catalyzed Annulation of Triazoles and Internal Alkynes. Issue 42 (October 2015) - Zhao, Shixian; Yu, Ruicheng; Chen, Wanzhi; Liu, Miaochang; Wu, Huayue
Abstract Depending on the additive, 4‐aryltriazoles (I) are either annelated to the title compounds or vinylated at both ortho positions of the arene moiety relative to the triazole residue.